The Application of Organic Liquid Fertilizer of Chromolaena Odorata on Rice Plants - Jamilah Jamilah (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2017)
Community service activities have been conducted in Ikur Lubuk Urban Village, Padang Panjang Timur Subdistrict, Padang Panjang City, in March-July 2016. Activities are demonstration plots (demplot) by planting rice that is given Liquid Organic Fertilizer (LOF) and pruning treatment. The purpose of the devotion is to socialize the demonstration plot so that the community can apply the pruning technology of HMT (forage and livestock feed) and the application of LOF Crocober to the paddy field of medium elevation area, Padang Panjang, so as to obtain HMT and optimal dried rice yield. Activities including the demplot establishment and LOF production. The results of the activity concluded that Crocober organic fertilizer product derived from Chromolaena odorata is the best LOF type and has a better quality than commercial LOF which is distributed in the market and already have PATENT approval. Pruning can help provide HMT for cattle to cope with the high imports of Indonesian meat. Treatment of pruning on paddy rice will be advantageous if pruning is done periodically with the pattern of rice cultivation which is named by salibu. Forage which is obtained in the area of 1 hectare of rice fields per year is able to meet the needs of 2 cows for 1 year.